Health risk and disease burden of daily hospitalizations for vaginitis due to air pollution: evidence from a heavily-polluted-city in China - Roumei Lin; Yanhu Ji; Yueliang Chen; Xuefeng Su; Qiuyan Cai; Ziyi Song; Weichen Yao; Liping Li (BMC Public Health)
Abstract Background The impact of ambient air pollutants on gynecological infections, particularly vaginitis, has been minimally explored. Method Data were collected from a heavily polluted city in Central China from 2015 to 2017. We employed a Poisson generalized additive model (GAM) to evaluate the impacts of air pollutants on vaginitis hospitalizations. Effect modifications by age and season were further assessed via stratified analyses. Additionally, attributable fractions (AFs) and numbers (ANs) of hospitalizations due to air pollutant exceedances were calculated to further estimate the disease burden. Results A total of 13,828 hospitalizations for vaginitis were recorded. In general, the concentrations of PM2.5, PM10, SO2, and NO2 were significantly positively correlated with daily hospitalizations for vaginitis. Specifically, increases of 10 µg/m³ in PM2.5, PM10, and NO2 at lag01 were associated with RRs of 1.0107 (95% CI: 1.0023–1.0192), 1.0076 (95% CI: 1.0013–1.0139) and 1.0470 (95% CI: 1.0189–1.0759), respectively. The increase in SO2 at lag05 corresponded to an RR of 1.0131 (95% CI: 1.0047–1.0216). No significant effects were observed for O3 or CO on vaginitis. Stratified analyses indicated that the associations were stronger in the younger age group (20–39 years) and during the cold season (October–March). Furthermore, 18.42% of hospitalizations, equivalent to 2547 cases (95% CI: 1665, 3384), were attributable to ambient air pollutants according to the WHO air quality guidelines. Conclusion Short-term exposure to PM2.5, PM10, SO2, and NO2 significantly increased vaginitis hospitalization risks, particularly among younger women (20–39 years) and during the cold season (October–March). This suggests the need for air pollution reduction and health education for high-risk groups to minimize exposure to pollutants.